Optimization of Extraction Method for Easily Extractable Glomalin-Related Soil Protein from Calcareous Soil - Li JIANG; Zhiqiang KANG; Yueming LIANG; Zeyan WU; Chun TU; Qiang LI (Yankuang ceshi)
Glomalin-related soil protein (GRSP) secreted by arbuscular mycorrhizal fungi is widely distributed worldwide, has stable properties and is not easily decomposed, which is an important component of soil organic matter. Extracting high quality GRSP is important for in-depth research on organic carbon sinks in calcareous soil from karst areas. However, in previous studies, the mechanism of GRSP in organic matter could not be further studied due to low extraction yield, insufficient extraction and non-specific products. Therefore, the high extraction amount of GRSP is of great significance to explore the formation and stabilization mechanism of organic matter in calcareous soil. This experiment selected four types of calcareous soil from karst areas: black, brown, yellow and red calcareous soil. By using orthogonal experiments of temperature and time, the optimal extraction conditions for easily extractable glomalin-related soil protein (EE-GRSP) related to particulate organic matter (POM) and mineral-associated organic matter (MAOM) in calcareous soil were selected. The experimental results showed that the highest extraction amount of EE-GRSP was achieved when POM and MAOM were extracted at 123℃ and 80min. After application into the four types of calcareous soil, the EE-GRSP contents increased from 4.6% to 34.2%. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202402060015.